Analysis of volleyball lower passing skills in junior high school students - Islam, Maftuh; Lufthansa, Luthfie; Kurniawan, Rubbi; Junaidi, Ahmad; Hadi, Antonius Prasetyo (Universitas Suryakancana, 2025)
Sports activities are carried out once a week without a structured concept and seem boring. With the rarity of volleyball games, students when doing lower passes still encounter some difficulties. This research methodology uses a quantitative descriptive approach. Data collection using surveys, with the subjects in this study conducted on VII grade students of SMP Plus Al-Firdaus totaling 19 students. Research planning begins with the development of research instruments, namely observation sheets, rubrics for assessing lower passing techniques, and student motivation/enthusiasm questionnaires, as well as submitting a research permit application letter to the principal of SMP Plus Al-Firdaus. The steps in data collection are: 1) Students perform lower passes according to the teacher's instructions. 2) Each student is given the opportunity to do 10 times the lower pass. 3) Each trial is evaluated using an assessment rubric (aspects of technique, accuracy, and consistency). Data analysis using a quantitative descriptive approach, from the results of data analysis obtained the results of the volleyball lower passing skills test with an average score of 85 including Excellent with a total of 4 students, while those who obtained an average score of 77 in the good classification were 15 students. We can analyze that so far, the volleyball learning process, especially the basic lower passing techniques that have been given to students, is in the good category.